2012
DOI: 10.1248/cpb.c12-00519
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of 8-<i>epi</i>-Xanthatin and Biological Evaluation of Xanthanolides and Their Derivatives

Abstract: An enantioselective synthesis of 8-epi-xanthatin (9) has been accomplished starting from the bicyclic lactone 3, which has been used for the synthesis of other xanthanolides, sundiversifolide (4) and diversifolide (5), through a synthetic route without the use of a selenium species. Additionally we have evaluated antimicrobial activities of five natural xanthanolides and their derivatives. Although the synthetic xanthanolides did not show any activity against methicillin-resistant Staphylococcus aureus (MRSA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the same year, Martin et al, reported the first total synthesis of the (+)-8-epi-xanthatin starting from the commercially available ester in 14 steps with overall yield of 5.5% [ 86 ]. In 2008, Shishido et al, completed the enantioselective total synthesis of xanthatin by the construction of the vinyl functionality at C1 and the exo-methylene at C11 via the syn-elimination of selenoxides from an optically pure cis-fused bicyclic lactone, and then, they reported an enantioselective total synthesis of 8-epi-xanthatin ( 2 ) by developing a synthetic route without the stoichiometric selenium reagents in 2012 [ 87 , 88 ]. In 2012, Tang et al, developed a method to synthesize the enantiopure γ-butyrolactones via a controllable Wagner–Meerwein-type dyotropic rearrangement of cis-β-lactones and successfully applied it to prepare a number of xanthanolides [ 89 ].…”
Section: Synthesis Of Xanthanolidesmentioning
confidence: 99%
“…In the same year, Martin et al, reported the first total synthesis of the (+)-8-epi-xanthatin starting from the commercially available ester in 14 steps with overall yield of 5.5% [ 86 ]. In 2008, Shishido et al, completed the enantioselective total synthesis of xanthatin by the construction of the vinyl functionality at C1 and the exo-methylene at C11 via the syn-elimination of selenoxides from an optically pure cis-fused bicyclic lactone, and then, they reported an enantioselective total synthesis of 8-epi-xanthatin ( 2 ) by developing a synthetic route without the stoichiometric selenium reagents in 2012 [ 87 , 88 ]. In 2012, Tang et al, developed a method to synthesize the enantiopure γ-butyrolactones via a controllable Wagner–Meerwein-type dyotropic rearrangement of cis-β-lactones and successfully applied it to prepare a number of xanthanolides [ 89 ].…”
Section: Synthesis Of Xanthanolidesmentioning
confidence: 99%
“…In 2012, Shishido et al. reported the enantioselective synthesis of 8‐ epi ‐xanthatin ( 2 ) based on the above chemistry . Starting from key intermediate 87 , diene 99 was obtained through sequential deprotection, an Appel reaction, and a base‐promoted β‐elimination reaction.…”
Section: Syntheses Of Monomeric Xanthanolidesmentioning
confidence: 99%
“…273 Known xanthanolides have been found in Inula sericophylla 439 and Xanthium sibiricum. 386 An enantioselective synthesis of 8-epi-xanthatin has been described, 440 whilst syntheses of this lactone and other xanthanolides have been achieved using a controllable dyotropic rearrangement of cis-blactones. 441 The activity of xanthatin on gastric carcinoma cells 442 and lung cancer cells 443 has been investigated.…”
Section: Germacranementioning
confidence: 99%